Extreme weather understanding the science of hurricanes, tornadoes, floods, heat waves, snow storms, global warming and other atmospheric disturbances - Mogil, H. Michael (London New Holland, 2007)
Looks at the how's and why's behind the planet's most devastating natural events, including hurricanes, floods, tidal waves, tornadoes, and heat waves.--Source other than Library of Congress.
Keywords: Weather; Natural disasters; Climatology